Movement as a Somaesthetic Source of Subjectivity - Dobrowolski, Robert; Pezdek, Krzysztof (Frontiers in Psychology, 2021)
The paper discusses two opposite understandings of how the kinaesthetic experience of movement translates into the development of subjectivity. One of them, in which somatically experienced movement is regarded as a positive source of authentic self-fashioning, will be described within the framework of phenomenology. The other, which emphasises the inauthentic nature of movement, will be described in term of psychoanalysis. Subsequently, the two opposite interpretations will be discussed in the conciliatory perspective of aesthetic experience, in which the contradiction of spontaneity and conformity will be shown as a quasi-artistic factor which bolsters the dynamics of subjectivity development.